Peran Pemerintah Dalam Menyelamatkan Naskah Kuno Minangkabau Pasca Gempa Pada Untuk Pelestarian Budaya Masyarakat Minangkabau - Viola Dewi Putri Syarif (IAIN Ponorogo, 2015)
The manuscripts of Minangkabau has many content about society, lives, and rules, such as the story of the batle that happened at that time, infuential scholars, the natural disasters that have occurred,and traditional medicine, all of it be writen with beautiful handwriting letered Arabic and Malay. On September 30, 2009 an earthquake with a strength of 7.9 on the Richter scale destroyed half of West Sumatera regions, include the buildings of information centers,and the storage areas of ancient texts Minangkabau. That makes all of ancients texts lost and broken. These manuscripts are original publications and unparalleled. This research is to know how the government’s role in saving the post-earthquake ancient manuscripts, for cultural preservation society of Minangkabau. This study is qualitative, using interview, observationand documentation. This study shows that in the preservation of the collection of ancient manuscripts damaged after the earthquake, West Sumatera provincial government assisted by the National Library team in repairing damaged manuscripts collection. National library team brings 17 boxes of ancient manuscripts Minangkabau to be treated. And to replace the lost collection, the government is conducting a search of the ancient manuscripts in houses to the public because there are still many collection of ancient manuscripts held by the public.